Viver na pobreza : experiências, afetos e sentidos - Santos, Mônica Nogueira dos (2018)
Poverty is now recognized as a multidimensional phenomenon of complex conceptualization and measurement. People who live in such a social condition have been confirmed as important public target of the professional performance of the psychologist in Public Policies. The objective of this research was to investigate the experience of poverty as perceived by people living in this social condition and was developed with a descriptive-analytical qualitative approach and a pluri-methodological approach. 73 high-level professionals working in the basic protection of SUAS and 112 people from poor families enrolled in the CadÚnico participated in this study. The instruments used were 1) "Free Association of Words", 2) Questionnaire with open questions and 3) Interview with semi structured script. These produced three sets of data that were treated and analyzed according to the specificity of each. The set of words evoked in the first instrument was analyzed with the help of the openEvoc program, from which the prototypical analysis of the social representation for the objects "poor person" and "rich person" and "family" for SUAS professionals and for families in a situation of poverty. The responses of the questionnaire were analyzed using the "Content Analysis" feature from which it was possible to understand the 'Affective dimension of living in the poverty condition' and the 'Metarrepresentation' of the object 'poor people' to non-poor people according to the members of poor families and finally the interviews, after being transcribed were analyzed according to a method of phenomenological inspiration for the empirical research in psychology which resulted in 18 individual and two group structures, corresponding to the first and second generation of families living in poverty . The results demonstrate that living in poverty does not only imply difficulties related to being materially poor, but also, and therein lies an important contribution of Psychology, implies in the sphere of social relations mobilizing affections / feelings and is related to a ' way of life 'corresponding to this social context that is passed from mother to child in an invisible and silent way in everyday relationships. It was also possible to broaden the understanding of the production context of the social representations studied here, as well as to exemplify social practices of maintenance or overcoming the poverty condition. Finally, this study demonstrated that it is essential to consider the structural determinations of poverty and the strategies of maintenance of social classes and not only to understand it as lack of income, that is, this problem must be understood from its relational scope, there is no space for individualization of social problems.